Why are toilets not used? Using system effects modelling to understand stakeholder perceptions on the impacts and barriers to Taenia solium control in Eastern and Western Uganda - Ngwili, Nicholas; Ahimbisibwe, Salaviriuse; Sentamu, D.N.; Craven, L.; Thomas, Lian F.; Roesel, Kristina (BioMed Central, 2025)
Taenia solium taeniasis/cysticercosis in humans and pigs remains endemic to Uganda. Although, looking at the lifecycle of the parasite, the risk factors are well known, and many biomedical control options exist – no substantial progress has been made in the eradication of T. solium infections in Uganda to date. Contextual factors including socioeconomic, cultural and infrastructural factors, may influence the adoption of interventions. A community-based study using mixed methods and relying on system effects modelling approach was carried out between March and April 2021 in Kamuli district, Eastern Uganda, and Hoima district, Western Uganda. System effects modelling is a non-linear methodology that captures the varied nature of the unique, individually lived experiences and aggregates them to reflect what is experienced at a population level. The aim of the study was to capture individual stakeholder perceptions on the consequences of T. solium infections and barriers to practice known control options. Overall, 27 factors were identified by 192 participants as consequences of being infected with neurocysticercosis (NCC). For taeniasis, 35 factors were identified with 700 edges/connections made by the participants. Enlargement of stomach, weight loss, diarrhoea, weakness, and stunted growth were the most important consequences. Although porcine cysticercosis (PCC) seemed to be poorly understood by the participants, 14 factors were identified which included poor pig growth, loss of market for pig/pork, and poor pork quality. The study also identified important barriers hindering the adoption of control practices, including lack of knowledge on transmission, sociocultural factors, and resource constraints. For women, lack of knowledge on the mode of transmission and lack of a toilet in the compound ranked highly as important barriers with a weighted degree of 31 and 21, respectively, meaning they were identified by more participants unlike men who ranked lack of a toilet first with a weighted degree of 39, followed by lack of knowledge at 24. Different barriers are associated with the adoption of T. solium control practices among community members, stakeholders, and farmers. Despite efforts to address T. solium infections, misconceptions and limited understanding persist among stakeholders, particularly regarding NCC and its associated consequences. The system effects approach supports developing contextualized interventions to help in the control of the diseases associated with this parasite.